Challenges of Green Office Implementation: A Case Study in Penang, Malaysia - Ong , Yee Sin; Yusof, Nor'Aini; Osmadi, Atasya (International Journal of Sustainable Construction Engineering and Technology, 2021)
This study was conducted in response to the lack of green office buildings in Malaysia, despite the fact that the green concept has been initiated in Malaysia for many years. The Penang State Government has taken the initiative to establish the Penang Green Council (PGC) as the first state in Malaysia, and the implementation of green offices is one of its programme initiatives. Nonetheless, green offices are still in scarcity across Penang. This study identified the challenges faced in implementing green offices. Data were collected from five green building owners using semi-structured interviews and the data were analysed using thematic analysis. The outcomes revealed that the main challenges faced by green office adoption were lack of budget, lack of awareness, lack of expertise, ownership factor, and type of building. This study offers several implications for practitioners and policy makers to improve the adoption of green office in Malaysia. The results may be applied to raise awareness amongst practitioners and office owners regarding green practices in office buildings. The study outcomes may serve as reference to policy makers on enhancing the development of green buildings.